Access to justice in times of AI: towards a low-cost justice? - Marta Cantero Gamito (Revista CIDOB d'Afers Internacionals)
Current discussions on the introduction of artificial intelligence (AI) into the courts, also reflected in policymaking, have largely focused on safeguarding fairness, transparency, explainability and human oversight in decision-making, including judicial decisions. However, in parallel with the question of whether AI can solve the judiciary’s crises of efficiency, the forthcoming transformation of the judiciary should be reconceptualised from the perspective of access to justice. This paper is an attempt to problematise the use of AI in the courts against the backdrop of the (access to) justice crisis in an economy focused on immediacy and a low-cost consumption model.